Pengaruh Perbedaan Gender dan Independensi Auditor Terhadap Kualitas Audit: Studi pada Auditor Eksternal di Kota Bandar Lampung - Utama, Fikri Rizki; Ardana, Yudhistira (Jurnal Eksplorasi Akuntansi, 2025)
This research aims to find empirical evidence of gender differences and auditor independence on audit quality. The population selected was all Public Accounting Firms in Bandar Lampung. Data collection techniques include distributing questionnaires directly and using google forms. Research data was processed using the Partial Least Square (PLS) program, namely Smart-PLS version 3.3.9. Empirically, the results of this study show that auditor gender differences have no influence on audit quality . Meanwhile, independence has a significant influence on audit quality. This independence is reflected in his ability to carry out audit tasks without being influenced by personal interests, without being pressured into decision-making, and without being influenced by external intimidation. The respondents used as the research population were only external auditors in the Bandar Lampung city area, so in the future it is necessary to expand the distribution of respondents to other cities as well. And also need to add other variables such as audit fees to audit quality because the amount of compensation (audit fee) received by the auditor will increase motivation for audit assignments. The findings in this research have several contributions, especially for external auditors in carrying out their audit duties. And hopefully this research will be useful for academics, especially further research.